Dimensi Amalan Etika Profesion - Shamsuddin Ahmad,; Khairuddin Idris,; Azahari Ismail, (Universiti Kebangsaan Malaysia, 2009)
A crisis of confidence in the society is partly due to the reason that the society increasingly feels that their interests are not served by the professions. The situation if allowed to continue will not only adversely affect the professions, but will also destabilize the society. This study aims to identify the dimensions of ethical practices among the teaching profession at a public institute of higher learning. Quantitative data were collected from 147 lecturers to determine the basic concept of ethics, while qualitative data were collected through interviews to understand ethical practices. Results from the quantitative study indicate that the respondents opined that ethics can be learned and attitudes were the determinants of ethical practices. Ethical practices were based on spiritual intelligence developed through education at home and the workplace. Qualitative findings showed that the dimensions of ethical practices are founded on religion and values, followed by epistemological foundations and competencies, and practiced through operational and contextual fundamentals. These three dimensions are interrelated and influence each other. Dilemmas on ethical decision making are addressed through strong principles and practiced at each of these dimensions. The implications are directed toward formal and non-formal training of lecturers on spiritual aspects throughout the career of the lecturers